MOTIVASI MASYARAKAT DALAM MENGIKUTI PENGAJIAN DI MAJLIS TAKLIM MASJID NURUL HUDA DESA BOTO SEMANDING TUBAN - Muslimin (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2018)
This study used a qualitative approach in descriptive form, and aimed to determine the kinds of motivations of the community to take part in the study at the Taklim Majlis Nurul Huda, Boto Village, Semanding District, Tuban, and to find out the level of community motivation to take part in the Majlis Taklim Nurul Huda Boto Village. This research is a field research, which directly examines the place of research in the majlis taklim Nurul Huda Mosque located on RT.01 RW.01 Boto village. The subjects in this study were pilgrims from the Taklim Nurul Huda Islamic Boarding School in Boto Village, namely the data sources were 35 worshipers and 3 administrators and 5 teachers or caregivers of the Majlis Taklim Nurul Huda. While the object of this research was the motivation of the community to attend the recitation in the mjelis taklim Nurul Huda, Boto village, Semanding. Then in the technique of collecting data by means of observation, interviews, questionnaires, to caregivers of the majelis taklim, administrators of the majlis taklim, the congregation and the people who live around the taklim assembly. Based on the results of the study it can be concluded that the motivation of the community to follow the recitation is very diverse. Like biogenetic motivation, sociogenetic motivation and theogenetic motivation. That is to increase the knowledge of religion, socialize with fellow citizens, also be an example of the example of the surrounding community in participating in the recitation, following the recitation can make themselves happy and comfortable, can strengthen the relationship, feel close to Allah SWT, and get inner peace, then following the recitation has become a necessity for a devout Muslim to Allah SWT, and added diligently to worship to Allah SWT after attending the recitation activity in the majlis taklim Nurul Huda, Boto Village. And regarding the level of motivation of the community to take part in the recitation in the Taklim assembly of Nurul Huda, Boto Village, it was classified as high and quite good seen from the biogenetic, sociogenetic and theogenetic theories.